The Effect of Strengthening The Character Education of The "TADZKIROH" Perspective on The Religious Character of Students - Anaas Tri Ridlo Dina Yuliana; Zalik Nuryana (Al-Misbah (Jurnal Islamic Studies), 2022)
Globalization which is overgrowing in various fields, has many impacts. The most often impact in the spotlight is related to character issues. As one of the agents of change and character control, educational institutions respond by implementing character education programs. The purpose of this study was to analyze the effect of strengthening character education from the "tadzkiroh" perspective on the religious character of students. This research approach uses quantitative associative evaluative research methods. From the research population at Muhammadiyah 1 Wates Vocational School, samples were taken from class XI, which amounted to 107 students, and then a sample of 84 students was taken. The sampling technique used is simple random sampling and proportional random sampling. Data collection techniques used are questionnaires and documentation. The data analysis technique was carried out descriptively in frequency analysis and cross tables and inferentially including correlation analysis and linear regression. The results showed that the level of character education in Tadzkiroh's perspective was effective with 69%, while the level of students' religious character was in the high category with 79,8%. The relationship between tadzkiroh perspective character education and students' religious character is quite significant with a correlation coefficient value of 0,507 or is in the medium category. The contribution of Tadzkiroh's perspective character education in predicting students' religious character is 25,7%, while the remaining 74,3% is contributed by other variables not examined in this study.